Tempelhof - park wolności, przykład adaptacji lotniska na park kulturowy = Tempelhof - freedom park, the example of airport adaptation for the purposes of cultural park - Janicka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Tempelhof Airport - formerly one of the biggest European airports, for many years the crucial airport of Berlin, recently aroused many disputes among inhabitants. After few years of debates, finally on the 6th of March 2013, Master Plan ? Area Development Plan was approved, which might allow to assume that it will be one of the most interesting European spatial investments of the centers of the cities in the next decade.
Keywords: Tempelhof; park kulturowy; rewitalizacja; plan zagospodarowania; konsultacje społeczne; Berlin; cultural park; revitalisation; area development plan; public consultation